Testing the tax competition theory: How elastic are national tax bases in Western Europe? - Aleksandra Riedl; Silvia Rocha-Akis (Oesterreichische Nationalbank (OeNB), 2008)
In this paper, we test one of the fundamental assumptions in the tax competition literature, namely, that a country's taxable income depends on the tax policies pursued in the domestic and in neighbouring countries. Based on a panel of annual data of 14 Western European countries spanning the period 1982 to 2004, we show that the common trend in falling corporate income tax (CIT) rates can in part be explained by the existence of fiscal externalities in the form of international resource flows. Our results confirm the presumption put forward in recent empirical tax reaction function studies, that interdependent tax setting behaviour is evidence of tax competition. However, taxable corporate income is shown to react inelastically to domestic and to foreign tax rates. Thus, the observed rise in CIT revenues in Europe between 1982 and 2004 cannot be explained by the trend in falling CIT rates. Moreover, we find that large countries' tax bases are more responsive to neighbouring countries' tax policies, which is in contrast to the classic asymmetric tax competition literature.
Keywords: H71; H72; H77; H87; C21; C23; 330; tax competition; corporate income tax base elasticity; asymmetric countries; instrumental variables; spatial econometrics